An Analysis of Case Grammar in English Film Dialogue: A New Perspective of Linguistic Modern - Basid, Abdul; Arzaqi, Arga Zidan; Romadani, Fadzilah; Miolo, Syahrul Alfitrah (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2023)
Abstract. Fillmore is modern linguistic figure who pioneered the emergence of case grammar theory. He stated that case grammar is a new version of the theory modified from the old theory, namely generative transformation grammar. He developed case grammar after seeing a problem with the grammar of generative transformations. Thus, he declared that case grammar consists of two basic components: modality and proposition. In a line with this background, the purposes of this study are: (1) to reveal the modality in the film “Enola Holmes” based on the perspective of Charles J. Fillmore; (2) to reveal the preposition in the film “Enola Holmes” based on the perspective of Charles J. Fillmore. The type of this study is qualitative descriptive study. Data is in the form of conversation in the film. Thus, the data were taken through watching, listening, and note-taking techniques. The data was analyzed by using three steps. They are data reduction: researchers classified data based on elements of case grammar theory including modalities and propositions, data presentation: researchers displayed data in the form of the table in accordance of modalities and propositions, and interpreted data based on case grammar theory, and conclusion: researchers conducted data induction from interpretation results and ensured that the interpretation results fulfilled the elements of case grammar theory. The results show that the modality in the film “Enola Holmes” based on the perspective of Charles J. Fillmore consists of three modalities. They are tense modality, adverb modality, and negation modality. At the same time, the proposition consists of ten types. They are agentive case (A), experiential case (E), instrument case (I), objective case (O), source case (S), goal case (G), locative case (L), time case (T), companion case (CMP), and benefactive case (B). The results of this study strengthen Fillmore’s theory which states that as a part of sentence structures, modalities and propositions have types and forms and in the context of English film dialogue, the emergence of modalities and propositions is influenced by sentence structure used by the speaker in conveying his meaning.Keywords: Case Grammar, Film, Modality, Proposition